Monkey and Me - Gravett, Emily (London : Macmillan Children's Books, 2007)
A little girl imitates a variety of animals, from bats to penguins to kangaroos, with her stuffed toy monkey.
1.2
K-3.
K-3
Keywords: Monkeys -- Juvenile fiction; Stuffed animals (Toys) -- Juvenile fiction; Zoo animals -- Juvenile fiction; Monkeys -- Fiction; Stories in rhyme; Stuffed animals (Toys) -- Fiction; Zoo animals -- Fiction; Monkeys -- Fiction; Stories in rhyme; Stuffed animals (Toys) -- Fiction; Zoo animals -- Fiction; Picture books for children